Method for pre-sintering ceramsite by using chain grate

By adopting the chain grinder presintering process in solid waste recycling, combined with high-temperature roasting of rotary kiln and cooling of cooler, the problems of high-volume production cost and low efficiency are solved, and the production of high-capacity and high-quality ceramics are achieved. .

CN119390472APending Publication Date: 2025-02-07UNIV OF SCI & TECH BEIJING
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411454230.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, solid waste recycling and processing into ceramic granules is high, the equipment structure is complex, and the fuel is single, resulting in low production efficiency and quality of ceramic granules.

Method used

The method of presintering ceramates is performed by using a chain grinding machine. By crushing solid waste and natural minerals and granulating, it is presintered at 800-1000°C through the drying, preheating and decarbonizing section of the chain grinding machine, and then rotating. High-temperature roasting is carried out in the kiln and finally cooled in a cooler to prepare high-quality ceramic granules.

Benefits of technology

The ceramic pellet production line has achieved a production capacity of hundreds of thousands to million tons, while reducing fuel consumption and production costs, improving the performance uniformity and heat recycling rate of ceramic pellets.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a method for pre-sintering ceramsite by using a chain grate, and relates to the technical field of solid waste recovery, and the method comprises the following steps: crushing solid waste, and granulating to prepare ceramsite green pellets; the ceramsite green pellets are conveyed to a chain grate machine and evenly distributed, then pass through a drying section, a decarburization section and a preheating section and are sintered at the temperature of 850-1000 DEG C, and hot-state pre-sintered ceramsite is obtained; feeding the hot pre-sintered ceramsite into a rotary kiln for high-temperature roasting at the temperature of 1120-1190 DEG C, and cooling in a cooling machine to obtain a ceramsite finished product. According to the method, the cost of recycling solid waste can be effectively reduced, the equipment structure is simple, fuel is diversified, and finished products produced from the rotary kiln can be high-strength ceramsite and can also be used for producing sintered and expanded ceramsite; and the pre-sintered ceramsite can be directly used as a porous ceramsite finished product to be applied to the fields of moisturizing, reclamation, water treatment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste recycling, and in particular to a method for pre-sintering ceramsite using a chain grate machine. Background Art

[0002] my country provides about half of the world's coal, electricity, metal and non-metal products, and also emits about half of the world's industrial solid waste. Among them, my country's corresponding emissions of steel slag, red mud, ferroalloy slag, fly ash, etc. exceed half of the world, and coal gangue, copper slag, etc. are close to half of the world. At present, the overall utilization rate of industrial solid waste in my country is less than 60%, and the total stockpile volume is tens of billions of tons, which not only occupies a large amount of land, but also poses serious safety and environmental pollution risks. To achieve green development of the industrial system, it is urgent to realize the large-scale utilization of industrial solid waste.

[0003] In my country, the annual consumption of sand and gravel aggregates exceeds 15 billion tons, the consumption of concrete is about 6 billion tons, and the annual consumption of cement is 1.3 billion tons. For industrial solid waste that is difficult to use in the fields of cement and concrete, using it as sand and gravel aggregates is the most effective way to utilize it on a large scale.

[0004] Using solid waste to prepare expanded clay to replace sand and gravel aggregates is an effective way to utilize solid waste on a large scale. It is also an important direction for the green transformation and development of waste-producing enterprises and building materials enterprises, and has become a focus of industry attention. Most of my country's expanded clay adopts the rotary kiln calcination process, which can produce swelled expanded clay and high-strength expanded clay, but it has never solved the problems of small output, low green strength, small amount of solid waste, and low thermal efficiency. This has led to the current maximum single-line production capacity of rotary kiln calcined expanded clay of only 100,000 tons / year, and a fuel consumption of 60-120 kg of standard coal / ton of finished product. Therefore, the current rotary kiln expanded clay is mainly swelled clay, with low density and high price. It is mainly used in functional occasions such as thermal insulation, lightweight, and sound insulation, with a market volume of about 15 million tons / year.

[0005] To reduce the production cost of ceramsite, it is necessary to further expand the production capacity of ceramsite single-line equipment and improve the efficiency of heat recycling. Drawing on the experience of the steel industry's sintering machines or roasting machines, which can expand production capacity to hundreds of thousands to millions of tons, while saving more than half of the fuel consumption compared to traditional rotary kilns, a process technology for preparing ceramsite using the principles of sintering machines or roasting machines has emerged.

[0006] Among them, the research and industrial application of fly ash ceramsite in traditional sintering machines show that this method makes full use of the internal heat of ceramsite for combustion, which greatly reduces combustion. However, the inherent left-right and up-and-down temperature differences and different calcination times of the sintering machine lead to uneven and unstable performance of ceramsite, which greatly affects the engineering application of fly ash sintered ceramsite. Currently, there are very few production lines on the market using this technology.

[0007] The newly developed expanded clay roasting / cooling method that draws on the metallurgical pellet roasting process or tunnel kiln process includes tunnel kiln expanded clay roasting equipment, static roasting furnace, belt-type solid waste expanded clay roasting machine, translational solid waste expanded clay roasting machine, etc. The products prepared by these methods are mainly high-strength expanded clay or ordinary sintered expanded clay, and cannot be fired into expanded clay. Moreover, burners using pulverized coal, biomass or heavy oil cannot be used, which results in relatively single products and a single fuel type. Summary of the invention

[0008] The invention provides a method for pre-sintering ceramsite by using a chain grate machine, so as to solve the technical problems in the prior art of high cost, complex equipment structure and single fuel for recycling solid waste into ceramsite.

[0009] In order to achieve the above-mentioned invention object, the technical solution provided by the present invention is as follows:

[0010] A method for pre-sintering ceramsite using a chain grate machine comprises the following steps:

[0011] S1. crushing solid waste and / or natural minerals and granulating them to prepare ceramsite green balls;

[0012] S2, transport the ceramsite raw balls to the chain grate and evenly distribute them, and then go through the drying section, decarbonization section and pre-

[0013] In the hot section, pre-sintering is performed at 800-1000°C to obtain hot pre-sintered ceramsite;

[0014] S3, sending the hot pre-sintered ceramsite into a rotary kiln for high-temperature roasting, wherein the temperature of the high-temperature roasting is 1120-1190° C., and cooling in a cooler to obtain a finished ceramsite product.

[0015] Preferably, the solid waste in S1 is coal gangue, tailings, contaminated soil, steel slag, fly ash,

[0016] One or more of gasified slag, red mud, sewage sludge, copper slag, construction waste, oil sludge, and slag; the natural mineral is one of clay and shale.

[0017] Preferably, the ceramsite green balls in S1 are formed by disc forming or extrusion forming, the diameter of the disc-formed ceramsite green balls is 4.75-19 mm, and the diameter of the extrusion-formed cylindrical ceramsite green balls is 12 mm and the length is 15-18 mm.

[0018] Preferably, the ceramsite raw ball described in S1 has a compressive strength greater than 150N and is not damaged after being dropped from a height of half a meter five times.

[0019] Preferably, the ceramsite green balls in S1 have a dry basis calorific value greater than or equal to 300 kcal / kg, which are high calorific value green balls, and the thickness of the high calorific value green balls on the chain grate is 260-380 mm.

[0020] Preferably, the ceramsite green balls in S1 have a dry basis calorific value of less than 300 kcal / kg, which are low calorific value green balls, and the thickness of the low calorific value green balls on the chain grate is 200-260 mm.

[0021] Green balls with high calorific value need to burn themselves, just like the layer combustion of sintered ore or coal. This requires the formation of a combustion layer in the material layer. Since the combustion layer burns from top to bottom, the thicker the material layer, the less impact on energy consumption. However, the combustion layer speed cannot be too fast, otherwise it will release too much heat and cause overheating. The combustion speed of the low calorific value combustion layer can be faster, and the heat released is not large, so it will not overheat. Therefore, high calorific value and thick material layer correspond to low speed and long time sintering; low calorific value and thin material layer correspond to fast and short time sintering. In the end, the sintering speed of low calorific value raw materials may be fast, but the high calorific value output has more waste heat.

[0022] Preferably, the chain grate in S2 is one of a two-stage chain grate, a three-stage chain grate, a decarbonization three-stage chain grate, and a four-stage chain grate. The two-stage chain grate includes an exhaust drying section and a preheating section, and is used to process low calorific value raw balls with a moisture content lower than 9%; the three-stage chain grate includes a blast drying section, an exhaust drying section, and a preheating section, and is used to process low calorific value raw balls with a moisture content not lower than 9%; the decarbonization three-stage chain grate includes an exhaust drying section, a decarbonization 1 section, and a decarbonization 2 section, and is used to process high calorific value raw balls with a moisture content lower than 9%; the four-stage chain grate includes a blast drying section, an exhaust drying section, a decarbonization 1 section, and a decarbonization 2 section, and is used to process high calorific value raw balls with a moisture content not lower than 9%.

[0023] When the moisture content is high, if the heating rate is fast, too much water vapor will be released inside, which will cause the green balls to burst. Therefore, green balls with high moisture content need to be cooled slowly. Green balls with a moisture content greater than 9% are prone to bursting at temperatures below 150°C. They need to be dried in a separate blast drying section, cooled slowly, and their moisture content reduced to 9% or lower, and then enter the subsequent exhaust drying section to dry at a faster speed.

[0024] Preferably, the hot pre-sintered ceramsite in S2 has a compressive strength greater than 300N, a calorific value less than 90kcal / kg, and a bulk density of 705-1055 kg / m 3 .

[0025] Preferably, the hot pre-sintered ceramsite in S2 can be used as a raw material for producing moisture-retaining ceramsite with an open-pore structure or a water treatment filter material.

[0026] Preferably, the bulk density of the ceramsite finished product is 450-1185 kg / m 3 The finished ceramsite can be used as artificial sand and gravel aggregate for structural and non-structural buildings, common high-strength ceramsite used in civil engineering, or expanded ceramsite with heat-insulating and lightweight characteristics.

[0027] Compared with the prior art, the present invention has at least the following beneficial effects:

[0028] 1. The present invention is different from the traditional rotary kiln process for preparing ceramsite. The traditional process involves drying, pre-sintering and decarburizing the ceramsite before 1000°C. The problems of slow reaction, high uniformity requirements, difficult atmosphere control, and easy breakage of the raw balls due to the raw balls falling have greatly restricted the output and quality of ceramsite fired in the rotary kiln. The current production capacity is only at the level of 10,000 tons or 100,000 tons. The present invention draws on the metallurgical chain grate machine-rotary kiln process and innovatively uses the chain grate machine heating method in the drying, pre-sintering and decarburization process. The ceramsite raw balls are spread flat on the grate plate of the chain grate machine and moved horizontally. The balls are heated by exhausting air up and down. This makes the heating uniformity of the ceramsite raw balls strong and not easy to break. The heating air volume, air temperature and atmosphere are easy to control. The drying, sintering, decarburization and other reactions of the ceramsite in the heating process are uniform and controllable, with high reaction efficiency, short reaction time and large production capacity. The present invention ensures that the production line of expanded clay reaches the level of hundreds of thousands of tons to millions of tons. At the same time, the chain grate machine used in the present invention can flexibly supply the heat source for heating according to the characteristics of the heat required by the raw materials at different stages, using the hot flue gas discharged from the high-temperature roasting section rotary kiln or the hot air from the high-temperature expanded clay cooling process, which makes it have a higher heat recycling rate and lower fuel consumption than the traditional rotary kiln process.

[0029] 2. The present invention is different from the traditional sintering machine, tunnel kiln or roasting machine for preparing ceramsite. In combination with the characteristics of ceramsite raw materials, the process characteristics of chain grate machine, rotary kiln and cooler are fully utilized. The chain grate machine does not need to lay the bottom material, and the output efficiency is higher. Compared with the belt roasting machine, the cloth thickness of the chain grate machine in the drying and preheating stages, the rotation speed / partition of the rotary kiln in the roasting stage, the thickness of the cooler material layer in the cooling stage, etc., as well as the corresponding process time can be changed more flexibly, thereby ensuring that the ceramsite firing process in each typical process section has strong raw material adaptability and the highest efficiency.

[0030] Compared with the sintering machine and roasting machine process, the problem of uniform quality of ceramsite during high-temperature roasting is solved. The high-temperature calcination process of the rotary kiln is adopted. After pre-calcination by the chain grate machine, the ceramsite with a certain strength is not easy to break when it falls and rolls in the kiln. It can avoid the adhesion of ceramsite under the high temperature of the sintering machine or roasting machine, and the gradient of the atmosphere and temperature field between the upper and lower material layers that is difficult to control. The prepared ceramsite has the characteristics of more uniform and stable performance. The ceramsite products can be sintered ceramsite, expanded ceramsite and other types and density grades.

[0031] 3. The present invention draws on the process of chain grate machine-rotary kiln-cooler in the metallurgical industry, and proposes to combine the exhaust (blast) roasting method that comprehensively considers high efficiency and high heat recycling rate with the rotary kiln calcination with rich fuel and product types, so as to achieve not only the roasting capacity of solid waste ceramsite of the order of 100,000 tons to 1 million tons and low fuel consumption cost, but also the production of multiple types of ceramsite products such as sintering and sintering, and the use of multiple types of fuel. The fuel is diverse, and the characteristics of the rotary kiln are utilized. Not only can gas fuels such as natural gas and coal gas be used, but also solid or liquid fuels such as coal powder, biomass, water-coal slurry or heavy oil can be easily switched.

[0032] 4. Metallurgical enterprises have a large number of million-ton chain grate rotary kilns that need to be eliminated. The old chain grate rotary kilns can be transformed according to the present invention and applied to the resource recycling industry of preparing ceramsite from solid waste. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] Steel slag, fly ash and construction waste are ground and granulated, and screened using gravel sieves with apertures of 16mm and 9.5mm. The 9.5-16mm particle size fraction is taken as qualified green balls, with a calorific value of less than 50kcal / kg, a compressive strength of 178N and the requirement of not breaking after falling from a height of half a meter five times. The ceramsite green balls are laid in a chain grate machine to a thickness of 220mm, and heated in three stages: blast drying, exhaust drying and preheating. The hot air from the low-temperature section of the high-temperature ceramsite is used to heat the blast drying section by using a cooler, and the hot air from the preheating section is used to heat the exhaust drying section. The flue gas at the outlet of the rotary kiln directly enters the preheating section to heat the ceramsite. The pre-sintering temperature is 850℃. The performance of the ceramsite sampled at the outlet of the preheating section is 355N in compressive strength, 0 in calorific value, and 915 kg / m 3 The highest temperature of the rotary kiln is 1150℃, and the rotary kiln uses coal powder as fuel. After leaving the rotary kiln, the ceramsite enters the ring cooler for cooling. The hot air from the high temperature section of the cooler is sent to the rotary kiln as secondary air, and the hot air from the low temperature section is sent to the blast drying section. The bulk density of the finished ceramsite after cooling is 995 kg / m 3 , the cylinder pressure strength is 7.2MPa.

[0036] Example 2

[0037] Steel slag, tailings, contaminated soil and construction waste are ground and granulated, and screened using gravel sieves with apertures of 19mm and 9.5mm. The 9.5-19mm particle size fraction is taken as qualified green balls, with a calorific value of less than 50kcal / kg, a compressive strength of 185N and the requirement of not breaking after falling from a height of half a meter five times. The ceramsite green balls are laid in a chain grate machine to a thickness of 260mm, and heated in three stages: blast drying, exhaust drying and preheating. The hot air from the low-temperature section of the high-temperature ceramsite is used to heat the blast drying section by using a cooler, and the hot air from the preheating section is used to heat the exhaust drying section. The flue gas at the outlet of the rotary kiln directly enters the preheating section to heat the ceramsite. The pre-sintering temperature is 1000℃. The performance of the ceramsite sampled at the outlet of the preheating section is 420N in compressive strength, zero in calorific value, and 928 kg / m 3 The highest temperature of the rotary kiln is 1190℃, and the rotary kiln uses coal powder as fuel. After leaving the rotary kiln, the ceramsite enters the single-drum cooler for cooling. The hot air from the single-drum cooler is sent to the rotary kiln as secondary air, and then the ceramsite is further cooled in the belt cooler, forming a low-temperature section of hot air that is sent to the blast drying section. The bulk density of the finished ceramsite after cooling is 463 kg / m 3 , the cylinder pressure strength is 1.8MPa.

[0038] Example 3

[0039] The gangue is ground and granulated, and screened using a sand and gravel sieve with an aperture of 16mm and 9.5mm. The 9.5-16mm particle size fraction is taken as qualified green balls, with a calorific value of 573kcal / kg, a compressive strength of 155N, and meets the requirement of not breaking after falling from a half-meter height five times. The ceramsite green balls are laid in a chain grate machine to a thickness of 380mm, and a four-stage heating method of blast drying, exhaust drying, decarbonization stage 1, and decarbonization stage 2 is adopted. Among them, the low-temperature hot air of the high-temperature ceramsite is used to heat the ceramsite in the blast drying stage by using a cooler, and part of the hot air discharged from the decarbonization stage 2 is used to heat the ceramsite in the exhaust drying stage; most of the rich hot flue gas discharged from the decarbonization stage 2 is sent to the waste heat boiler for waste heat utilization. The flue gas discharged from the decarbonization stage 1 is sent to the decarbonization stage 2 for secondary combustion. At the same time, the flue gas at the outlet of the rotary kiln directly enters the decarbonization stage 2 to heat the ceramsite. The pre-sintering temperature is 950℃. The performance of the ceramsite sampled at the outlet of the decarbonization stage 2 is 598N in compressive strength, 75 kcal / kg in calorific value, and 915kg / m3 in bulk density. 3 The highest roasting temperature of the rotary kiln is 1160℃, and the rotary kiln uses pulverized coal as fuel. After leaving the rotary kiln, the ceramsite enters the annular cooler for cooling. The hot air from the high temperature section of the cooler is sent to the rotary kiln as secondary air after passing through the waste heat boiler, and the hot air from the low temperature section is sent to the blast drying section. The bulk density of the finished ceramsite after cooling is 995 kg / m 3 , the cylinder pressure strength is 8.9MPa.

[0040] Example 4

[0041] The coal gangue, gasified slag and shale are mixed and ground and granulated, and screened with a sand and gravel sieve with an aperture of 16mm and 9.5mm. The 9.5-16mm particle size is taken as qualified green balls, with a calorific value of 710kcal / kg, a compressive strength of 190N and the requirement of not breaking after falling from a half-meter height for five times. The ceramsite green balls are laid in a chain grate machine to a thickness of 300mm, and a four-stage heating method of blast drying, exhaust drying, decarbonization stage 1 and decarbonization stage 2 is adopted. Among them, the flue gas discharged from the waste heat boiler is used to heat the ceramsite in the blast drying stage, and the low-temperature hot air of the high-temperature ceramsite is used to heat the ceramsite in the exhaust drying stage by using a cooler; the rich hot flue gas discharged from the decarbonization stage 2 is sent to the waste heat boiler for waste heat utilization. The flue gas discharged from the decarbonization stage 1 is sent to the decarbonization stage 2 for secondary combustion, and the flue gas at the outlet of the rotary kiln directly enters the decarbonization stage 2 to heat the ceramsite, and the pre-sintering temperature is 950℃. The performance of the ceramsite sampled at the outlet of decarbonization stage 2 is as follows: compressive strength 408N, calorific value 92 kcal / kg, bulk density 908kg / m 3 The highest roasting temperature of the rotary kiln is 1170℃, and the rotary kiln uses pulverized coal as fuel. After leaving the rotary kiln, the ceramsite enters the annular cooler for cooling. The hot air from the high temperature section of the cooler is sent to the rotary kiln as secondary air after passing through the waste heat boiler, and the hot air from the low temperature section is sent to the blast drying section. The bulk density of the finished ceramsite after cooling is 991 kg / m 3 , the cylinder pressure strength is 11.8MPa.

[0042] Example 5

[0043] The coal gangue and steel slag are mixed and ground and granulated, and screened using a sand and gravel sieve with an aperture of 16mm and 4.75mm. The 4.75-16mm particle size portion is taken as qualified raw balls, with a calorific value of 360kcal / kg, a compressive strength of 181N, and meets the requirement of not breaking after falling from a half-meter height five times. The ceramsite raw material is laid in a chain grate machine to a thickness of 280mm, and a four-stage heating method of blast drying, exhaust drying, decarbonization 1 and decarbonization 2 is adopted. Among them, the hot air of the low-temperature section of the cooler is used, and the hot flue gas of the decarbonization 2 section is used to heat the ceramsite in the exhaust drying section. The flue gas discharged from the decarbonization 1 section is sent to the decarbonization 2 section for secondary combustion, and the flue gas at the outlet of the rotary kiln directly enters the decarbonization 2 section to heat the ceramsite, and the pre-sintering temperature is 980℃. The performance of the ceramsite at the outlet of the decarbonization 2 section after sampling is 378N in compressive strength, 81 kcal / kg in calorific value, and 905kg / m 3 The highest roasting temperature of the rotary kiln is 1180℃, and the rotary kiln uses biomass fuel. After leaving the rotary kiln, the ceramsite enters the single-drum cooler for cooling, and the high-temperature hot air from the cooler is sent to the rotary kiln as secondary air; then the ceramsite enters the belt cooler for cooling and transportation, and the low-temperature hot air is sent to the blast drying section. The bulk density of the finished ceramsite after cooling is 520 kg / m 3 , the cylinder pressure strength is 2.8MPa.

[0044] Example 6

[0045] The red mud and coal gangue are mixed and stirred and extruded into granules. The sand and gravel sieves with apertures of 16mm and 4.75mm are used for screening. The 4.75-16mm particle size is taken as qualified raw balls. The raw material with a length of 15mm has a calorific value of 320kcal / kg, a compressive strength of 278N and meets the requirement of not breaking after falling from a height of half a meter five times. The ceramsite raw material is laid in the chain grate to a thickness of 260mm, and a four-stage heating method of blast drying, exhaust drying, decarbonization stage 1 and decarbonization stage 2 is adopted. Among them, the hot air of the low temperature stage of the cooler and the hot air of part of the decarbonization stage 2 are used to heat the ceramsite in the blast drying stage, and the hot flue gas of the decarbonization stage 2 is used to heat the ceramsite in the exhaust drying stage. The flue gas discharged from the decarbonization stage 1 is sent to the decarbonization stage 2 for secondary combustion. At the same time, the flue gas at the outlet of the rotary kiln directly enters the decarbonization stage 2 to heat the ceramsite. The pre-sintering temperature is 910℃. The performance of the ceramsite sampled at the outlet of decarbonization stage 2 is as follows: compressive strength 522N, calorific value 41 kcal / kg, bulk density 886kg / m 3 The highest roasting temperature entering the rotary kiln is 1160℃, and the rotary kiln uses biomass fuel. After leaving the rotary kiln, the ceramsite enters the single-drum cooler for cooling, and the high-temperature hot air from the cooler is sent to the rotary kiln as secondary air; then the ceramsite enters the belt conveyor for transportation and blast cooling at the same time, and the cooled low-temperature hot air is sent to the blast drying section. The bulk density of the finished ceramsite after cooling is 450 kg / m 3, The cylinder pressure strength is 2.1MPa.

[0046] Example 7

[0047] The contaminated soil and sludge are mixed and extruded into granules to form raw materials with an average diameter of 12mm and an average length of 17mm. The dry basis calorific value is 180kcal / kg, the compressive strength is 220N, and it meets the requirement of not breaking after falling from a height of half a meter five times. The ceramsite raw balls are laid in the chain grate machine to a thickness of 180mm, and three-stage heating is adopted, namely, air drying, exhaust drying, and waste heat section. The hot air from the low temperature section of the cooler is used to heat the ceramsite in the air drying section, and the exhaust gas from the preheating section is used to heat the ceramsite in the exhaust drying section. The flue gas from the rotary kiln outlet directly enters the preheating section to heat the ceramsite, and the pre-sintering temperature is 900℃. The performance of the ceramsite after sampling at the outlet of the preheating section is 332N in compressive strength, 0 in calorific value, and 705kg / m 3 The highest roasting temperature entering the rotary kiln is 1150℃, and the rotary kiln uses biomass fuel. After leaving the rotary kiln, the ceramsite enters the ring cooler for cooling. The high-temperature hot air from the cooler is sent to the rotary kiln as secondary air, and the low-temperature hot air is sent to the blast drying section. The bulk density of the finished ceramsite after cooling is 810 kg / m 3 , the cylinder pressure strength is 4.8MPa.

[0048] Example 8

[0049] The copper slag and clay are mixed and granulated, and screened using a gravel sieve with an aperture of 16mm and 4.75mm. The 4.75-16mm particle size fraction is taken as qualified green balls, with a calorific value of 200kcal / kg, a compressive strength of 158N and the requirement of not breaking after falling from a height of half a meter five times, and a moisture content of 8.5%. The ceramsite green balls are laid in a chain grate machine to a thickness of 200mm, and a two-stage heating method of exhaust drying and preheating is adopted. The hot air in the low-temperature section of the high-temperature ceramsite is cooled by a cooler to heat the ceramsite in the exhaust drying section; at the same time, the flue gas at the outlet of the rotary kiln directly enters the preheating section to heat the ceramsite, and the pre-sintering temperature is 800℃. The performance of the ceramsite sampled at the outlet of the preheating section is 588N in compressive strength, 0 in calorific value, and 1055kg / m 3 The highest roasting temperature of the rotary kiln is 1120℃, and the rotary kiln uses coal powder as fuel. After leaving the rotary kiln, the ceramsite enters the annular cooler for cooling. The hot air from the high temperature section of the cooler is sent to the rotary kiln as secondary air, and the hot air from the low temperature section is sent to the blast drying section. The bulk density of the finished ceramsite after cooling is 1185 kg / m 3 , the cylinder pressure strength is 10.6MPa.

[0050] Example 9

[0051] The gangue and gasified slag are prepared into decarbonized ceramsite. The gangue and gasified slag are ground and granulated, and the 9.5-16mm particle size is selected as qualified green balls after screening with a sand and gravel sieve with an aperture of 16mm and 9.5mm. The calorific value is 760kcal / kg, the compressive strength is 172N, and it meets the requirement of not breaking after falling from a half-meter height five times. The green balls are laid in the chain grate machine to a thickness of 330mm, and four-stage heating is adopted, namely, blast drying, exhaust drying, decarbonization stage 1 and decarbonization stage 2. Among them, the low-temperature hot air of the high-temperature ceramsite is used to heat the blast drying stage ceramsite, and part of the hot air discharged from the decarbonization stage 2 is used to heat the exhaust drying stage ceramsite; most of the rich hot flue gas discharged from the decarbonization stage 2 is sent to the waste heat boiler for waste heat utilization. The flue gas discharged from the decarbonization stage 1 is sent to the decarbonization stage 2 for secondary combustion. The performance of the ceramsite sampled at the outlet of decarbonization stage 2 is as follows: compressive strength 308N, calorific value 35 kcal / kg, bulk density 875kg / m 3 The average temperature of the pre-sintered hot ceramsite from the chain grate is 930℃, and then it is directly cooled in the ring cooler. The hot air from the high temperature section of the cooler passes through the waste heat boiler and enters the decarbonization section 2, and the hot air from the low temperature section is sent to the blast drying section. The bulk density of the finished ceramsite after cooling is 875 kg / m 3 , can be directly used as raw material for ceramics, cement or ecological soil.

[0052] Example 10

[0053] The sludge and slag are prepared into decarbonized ceramsite. The sludge and slag are ground and extruded into granules to form raw materials with a diameter of 12mm and an average length of 18mm. The calorific value is 480kcal / kg, the compressive strength is 190N and it meets the requirement of not breaking after falling from a height of half a meter five times. The raw balls are laid in the chain grate machine to a thickness of 350mm, and four-stage heating is adopted, including blast drying, exhaust drying, decarbonization 1 and decarbonization 2. The low-temperature hot air of the high-temperature ceramsite is cooled by the cooler to heat the ceramsite in the blast drying section, and the hot air discharged from the decarbonization 2 section is used to heat the ceramsite in the exhaust drying section; the flue gas discharged from the decarbonization 1 section is sent to the decarbonization 2 section for secondary combustion. The performance of the pre-sintered ceramsite after sampling at the outlet of the decarbonization 2 section is 418N in compressive strength, 0 in calorific value, and 910kg / m 3 The average temperature of the pre-sintered hot ceramsite from the chain grate is 907℃, and then it is directly cooled in the ring cooler. The hot air from the high temperature section of the cooler passes through the waste heat boiler and enters the decarbonization section 2, and the hot air from the low temperature section is sent to the blast drying section. The bulk density of the finished ceramsite after cooling is 910 kg / m 3 , can be directly used as raw material for ceramics, cement or ecological soil.

[0054] Embodiment 11

[0055] The gangue is prepared into open-pored ceramsite. The gangue is ground and granulated, and the 4.75-16mm particle size is selected as qualified green balls after screening with a sand and gravel sieve with an aperture of 16mm and 4.75mm. The calorific value is 680kcal / kg, the compressive strength is 202N, and it meets the requirement of not breaking after falling from a height of half a meter five times. The green balls are laid in a chain grate machine to a thickness of 350mm, and four-stage heating is adopted, including blast drying, exhaust drying, decarbonization 1 and decarbonization 2. Among them, the high-temperature flue gas discharged from the decarbonization 2 stage is used to heat the blast drying stage ceramsite with part of the low-temperature flue gas after passing through the waste heat boiler, and the part of the high-temperature flue gas discharged from the decarbonization 2 stage and part of the low-temperature flue gas after passing through the waste heat boiler are mixed to heat the exhaust drying stage ceramsite; most of the rich hot flue gas discharged from the decarbonization 2 stage is sent to the waste heat boiler for waste heat utilization. The flue gas discharged from the decarbonization stage 1 is sent to the decarbonization stage 2 for secondary combustion. At the same time, the hot air from the cooling high temperature stage passes through the waste heat boiler and directly enters the decarbonization stage 2 to heat the ceramsite. The performance of the ceramsite sampled at the outlet of the decarbonization stage 2 is 428N in compressive strength, 105 kcal / kg in calorific value, and 938kg / m in bulk density. 3 The average temperature of the pre-sintered hot ceramsite from the chain grate is 976℃, and then it is directly cooled in the ring cooler. The hot air from the high temperature section of the cooler passes through the waste heat boiler and enters the decarbonization section 2, and the hot air from the low temperature section is sent to the decarbonization section 1. The bulk density of the finished ceramsite after cooling is 938kg / m 3 , cylinder pressure strength is 2.7MPa, and it can be directly used as moisturizing ceramsite or water treatment filter material.

[0056] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. The protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for pre-sintering ceramsite using a chain grate machine, characterized in that: The following steps are involved: S1. crushing solid waste and / or natural minerals and granulating them to prepare ceramsite green balls; S2, transport the ceramsite raw balls to the chain grate and evenly distribute them, and then go through the drying section, decarbonization section and pre- In the hot section, pre-sintering is performed at 800-1000°C to obtain hot pre-sintered ceramsite; S3, sending the hot pre-sintered ceramsite into a rotary kiln for high-temperature roasting, wherein the temperature of the high-temperature roasting is 1120-1190° C., and cooling in a cooler to obtain a finished ceramsite product.

2. The method for pre-sintering ceramsite using a chain grate according to claim 1, characterized in that: The solid waste described in S1 is one or more of coal gangue, tailings, contaminated soil, steel slag, fly ash, gasification slag, red mud, sludge, copper slag, construction waste, oil sludge, and slag, and the natural mineral is one of clay and shale.

3. The method for pre-sintering ceramsite using a chain grate according to claim 1, characterized in that: The ceramsite green balls in S1 are formed by disc forming or extrusion forming. The diameter of the disc-formed ceramsite green balls is 4.75-19 mm, and the diameter of the extrusion-formed cylindrical ceramsite green balls is 12 mm and the length is 15-18 mm.

4. The method for pre-sintering ceramsite using a chain grate according to claim 1, characterized in that: The ceramsite green ball described in S1 has a compressive strength greater than 150N and is not damaged after being dropped from a height of half a meter five times.

5. The method for pre-sintering ceramsite using a chain grate according to claim 1, characterized in that: The ceramsite green balls described in S1 have a dry basis calorific value greater than or equal to 300 kcal / kg, which are high calorific value green balls. The thickness of the high calorific value green balls on the chain grate is 260-380 mm.

6. The method for pre-sintering ceramsite using a chain grate according to claim 1, characterized in that: The ceramsite green balls described in S1 have a dry basis calorific value of less than 300 kcal / kg, which are low calorific value green balls. The thickness of the low calorific value green balls on the chain grate machine is 200-260 mm.

7. The method for pre-sintering ceramsite using a chain grate according to claim 1, characterized in that: The chain grate described in S2 is one of a two-stage chain grate, a three-stage chain grate, a decarbonization three-stage chain grate, and a four-stage chain grate. The two-stage chain grate includes an exhaust drying section and a preheating section, and is used to process low calorific value raw balls with a moisture content lower than 9%; the three-stage chain grate includes a blast drying section, an exhaust drying section, and a preheating section, and is used to process low calorific value raw balls with a moisture content not lower than 9%; the decarbonization three-stage chain grate includes an exhaust drying section, a decarbonization 1 section, and a decarbonization 2 section, and is used to process high calorific value raw balls with a moisture content lower than 9%; the four-stage chain grate includes a blast drying section, an exhaust drying section, a decarbonization 1 section, and a decarbonization 2 section, and is used to process high calorific value raw balls with a moisture content not lower than 9%.

8. The method for pre-sintering ceramsite using a chain grate according to claim 1, characterized in that: The hot pre-sintered ceramsite in S2 has a compressive strength greater than 300N, a calorific value less than 90kcal / kg, and a bulk density of 705-1055 kg / m 3 .

9. The method for pre-sintering ceramsite using a chain grate according to claim 1, characterized in that: The hot pre-sintered ceramsite described in S2 can be used as a raw material for producing moisture-retaining ceramsite with an open-pore structure or a water treatment filter material.

10. The method for pre-sintering ceramsite using a chain grate according to claim 1, characterized in that: The bulk density of the finished ceramsite product is 450-1185 kg / m 3 The finished ceramsite can be used as artificial sand and gravel aggregate for structural and non-structural buildings, common high-strength ceramsite used in civil engineering, or expanded ceramsite with heat-insulating and lightweight characteristics.

Citation Information

Patent Citations

  • Kiln system and method for firing ceramsite containing calorific value raw materials and producing waste heat as byproduc

    CN112880394A

  • Method for preparing undoped single coal gangue ceramsite based on moving bed and ceramsite

    CN113105258A

  • Method for preparing high-strength lightweight aggregate by pellet roasting method

    CN114990329A

  • Method for preparing high-quality ceramic raw material by using calorific value-containing solid waste and application of high-quality ceramic raw material

    CN117247270A

  • Phosphorous Pentoxide Producing Methods and Systems with Increased Agglomerate Compression Strength

    US20160090305A1